SMALLHOLDER RICE FARMERS ACCESS TO RICE PRODUCTION INPUTS IN EKITI STATE, NIGERIA - Idowu, T.C.; Lawal, B.O.; Gabriel, D.A. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study examined smallholder rice farmers access to rice production inputs in Ekiti State, Nigeria.The specific objectives of the study were to: identify the socio-economic characteristics of the rice farmers and ascertain access to inputs for rice production activities in the study area. A multi-stage sampling procedure was used in selecting 135 and data were collected using structured questionnaire. Descriptive statistics such as frequency tables and percentages were used to achieve the research objectives. The result showed that majority (77.8%) of the respondents were male, 66.7% were married, and 65.2% had less than 2 hectares of land. The average farming experience in rice production was 30.8 years and 9 family members as the average household size. Furthermore, the study found respondents had access to simple farm tools (85.2%), rice seeds (92.6%), labour (82.2%) and fertilizers (59.3%). limited access to credit (), lack of awareness on inputs (), lack of access to market () and scarcity of recommended inputs () were among the constraints limiting access to inputs by the respondents. The respondents had access to different inputs for rice inputs for rice production but faced constraints in accessing inputs for their rice production. Therefore, it is recommended that government and relevant NGOs should subsidize the cost of farm inputs and strengthen extension services that will train rice farmers on the best methods of using farm inputs that will boost rice production in the country.